Ornamental Rhizoma Peanut: Perceptions and Use by Florida Consumers - Kelly M. Thomas; Ann R. Blount; Gary W. Knox; Cheryl L. Mackowiak; Lynn E. Sollenberger (HortScience, 2023)
Ornamental rhizoma peanut (Arachis glabrata Benth.; ORP) is a low-maintenance groundcover for use in urban and residential landscapes. Despite its availability since 2002, consumer insights on ORP have never been assessed. Online surveys are readily accepted by academic researchers as a valuable research tool. An online survey was distributed to 5820 Floridians with the objective to assess the use and perceptions of ORP by consumers. A total of 907 survey responses were received. Most respondents identified themselves as home gardeners (89%), white (93%), female (75%), and over age 65 (60%). Out of several turfgrass alternative benefits, respondents most valued reducing herbicide/pesticide and fertilizer/water usage and preventing weed establishment (χ2 = 204, df = 6, P < 0.001). The ORP selection purchased by respondents was predominately unknown. Most preferred ORP to flower heavily and frequently and maintain a canopy height below 20 cm in the landscape with infrequent mowing. Survey data show there is a potentially large consumer demand for ORP in Florida, but product availability, branding, and consumer access and engagement with information sources require additional focus in the coming years.